2014
DOI: 10.1002/term.1927
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of P19 embryonal carcinoma stem cells into insulin-producing cells promoted by pancreas-conditioned medium

Abstract: The ability of embryonal carcinoma )EC (stem cells to generate insulin-producing cells (IPCs) is still unknown. We examined the trophic effects of pancreas-conditioned medium (PCM) on in vitro production of IPCs. Initially, P19 EC cells were characterized by the expression of stem cell markers, Oct3/4, Sox-2 and Nanog. To direct differentiation, P19-derived embryoid bodies (EBs) were induced by selection of nestin-positive cells and treatment with different concentrations of PCM. Morphological studies document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 66 publications
4
17
0
Order By: Relevance
“…Furthermore, immunoreactivity for proinsulin along with C-peptide in the current study exhibited the presence of endogenously produced insulin. De novo synthesis and processing of insulin as a feature of normal b cells was reported previously (Brol en et al, 2005;Zulewski, 2006;Ebrahimie et al, 2014;Mansouri et al, 2014). In the current study, insulin production by IPCs was confirmed by immunoflourescence, ELISA, and real-time PCR analysis.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Furthermore, immunoreactivity for proinsulin along with C-peptide in the current study exhibited the presence of endogenously produced insulin. De novo synthesis and processing of insulin as a feature of normal b cells was reported previously (Brol en et al, 2005;Zulewski, 2006;Ebrahimie et al, 2014;Mansouri et al, 2014). In the current study, insulin production by IPCs was confirmed by immunoflourescence, ELISA, and real-time PCR analysis.…”
Section: Discussionsupporting
confidence: 86%
“…The imported genes in constructed network were CREB1 , EP300 , and PDX‐1 , which are the major regulators in differentiation of MSCs to IPCs. Interestingly, we observed the upregulation of these transcription factors at the following two experiments: (1) Production of IPCs from P19 EC stem cells under the treatment of PCM (Mansouri et al, ), and (2) Production of IPCs from P19 EC stem cells using mouse neonate pancreas extract (Ebrahimie et al, ). Upregulation of CREB1 , EP300 , and PDX‐1 transcription factors in production of IPCs from different types of stem cells, such as P19 EC stem cells and MSCs, and under different inducers, such as PCM and mouse neonate pancreas extract, confirms the key role of CREB1, EP300 , and PDX‐1 in generation of IPCs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations